2020
DOI: 10.3390/make2030012
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy-Based File Fragment Classification

Abstract: File fragment classification is an essential problem in digital forensics. Although several attempts had been made to solve this challenging problem, a general solution has not been found. In this work, we propose a hierarchical machine-learning-based approach with optimized support vector machines (SVM) as the base classifiers for file fragment classification. This approach consists of more general classifiers at the top level and more specialized fine-grain classifiers at the lower levels of the hierarchy. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In [ 40 ], the most important problem of forensics is solved in the form of classifying parts of files. For this, it is proposed to use a hierarchical approach using a set of optimized SVMs.…”
Section: Analysis Of Existing Review Workmentioning
confidence: 99%
“…In [ 40 ], the most important problem of forensics is solved in the form of classifying parts of files. For this, it is proposed to use a hierarchical approach using a set of optimized SVMs.…”
Section: Analysis Of Existing Review Workmentioning
confidence: 99%
“…Their results showed that as we increase the size of the fragments used for classification, the accuracy is increased. Also, if the fragment belongs to the start or the end of the file, the classification accuracy is higher as compared to a fragment taken from the middle of the file Bhatt, M [1] used a different classification technique than most others. Their approach was a mixture of clustering and classification.…”
Section: Survey Of Existing Systemsmentioning
confidence: 99%
“…Bhatt. M [1] used the Hierarchy-Based File Fragment Classification method. They classified simple file correctly but for complex file, often it failed to classify the specific type of complex file accurately.…”
Section: Limitations Of Existing Systemsmentioning
confidence: 99%
See 1 more Smart Citation